1985
DOI: 10.2105/ajph.75.12.1393
|View full text |Cite
|
Sign up to set email alerts
|

Diphtheria in the United States, 1971-81.

Abstract: After a decade-long resurgence, including a large cutaneous diphtheria outbreak in Washington State, the diphtheria incidence rate in the United States reached its lowest recorded level ever in 1980-two patients (0.01 case per million). Mortality paralleled the decline in incidence rate. Only 143 of the 3,141 US counties reported noncutaneous diphtheria patients during 1971-81; most were located in the West. The highest attack rates were experienced by children less than 15 years old (0.8 case per million) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…The reasons for the reduction of the number of tox-carrying C. diphtheriae strains in the NT are unclear, although it has been postulated that tox may be lost from organisms in highly immunized populations (3). The toxin gene is carried on a bacteriophage, but the toxin is a nonessential protein for both the phage and its lysogenic host bacterium (13).…”
mentioning
confidence: 99%
“…The reasons for the reduction of the number of tox-carrying C. diphtheriae strains in the NT are unclear, although it has been postulated that tox may be lost from organisms in highly immunized populations (3). The toxin gene is carried on a bacteriophage, but the toxin is a nonessential protein for both the phage and its lysogenic host bacterium (13).…”
mentioning
confidence: 99%
“…In the 1970s, nearly 1,300 cases of diphtheria in the United States (5) and 444 in Canada (3,6,9,19) were reported. Since the mid-1980s, the number of cases in both countries has declined to fewer than 50 (2,4,11,20).…”
mentioning
confidence: 99%
“…It was claimed m the medical literature that the spread of diphtheria in the community is prevented if 70-80% or more of the population is immune 8 . A recent WHO meeting concluded that to achieve the elimination of diphtheria, a minimum immunization coverage rate of 90% in children and 75% in adults is required 15 .…”
Section: Immunity To Diphtheria In the Populationmentioning
confidence: 99%